Analisis Hubungan Higiene Sanitasi dan Kualitas Bakteriologis Pada Depot Air Minum di Kecamatan Simbang Kabupaten Maros - Ashari Rasjid; Rasman Rasman; Nurhidayah Nurhidayah (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2026)
Drinking Water Depots (DAMs) are widely used by the community in Simbang District, Maros Regency, as an alternative source of daily drinking water; therefore, sanitation hygiene and bacteriological quality are important aspects of public health protection. This study aimed to analyze the relationship between depot sanitation hygiene and the bacteriological quality of produced drinking water. This research used an observational analytic design with a cross-sectional approach. The sample consisted of all 10 DAMs in Simbang District selected using total sampling. Primary data were collected through interviews, sanitation inspection observations, and laboratory examination of Total Coliform and Escherichia coli parameters. The results showed that 7 DAMs (70%) did not meet sanitation hygiene requirements, while 3 DAMs (30%) met the requirements. Bacteriological examination showed that 3 DAMs (30%) did not meet drinking water quality standards due to Total Coliform contamination ranging from 15–27 CFU/100 ml, while all samples were negative for E. coli. These findings indicate that poor sanitation hygiene conditions tend to be associated with bacteriological contamination in drinking water produced by DAMs. Improving sanitation practices, equipment maintenance, and operator hygiene is necessary to reduce the risk of microbiological contamination in refill drinking water.